2019
DOI: 10.2196/11917
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Following Use of a Smartphone Food Photo Feature: Retrospective Cohort Study

Abstract: Background Tracking of dietary intake is key to enhancing weight loss. Mobile apps may be useful for tracking food intake and can provide feedback about calories and nutritional value. Recent technological developments have enabled image recognition to identify foods and track food intake. Objective We aimed to determine the effectiveness of using photography as a feature of a smartphone weight loss app to track food intake in adults who were overweight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Longer intervention duration tempered this relationship, however, suggesting that self-monitoring may be less effective for weight loss over time either because engagement declines or because rates of weight loss slow despite similar degrees of engagement. This primary finding supports the conclusions from prior reviews that focused predominantly on paper-based selfmonitoring methods (26,27) and is also consistent with large-scale retrospective studies from industry platforms that used self-monitoring (85)(86)(87)(88)(89).…”
Section: Key Findingssupporting
confidence: 87%
“…Longer intervention duration tempered this relationship, however, suggesting that self-monitoring may be less effective for weight loss over time either because engagement declines or because rates of weight loss slow despite similar degrees of engagement. This primary finding supports the conclusions from prior reviews that focused predominantly on paper-based selfmonitoring methods (26,27) and is also consistent with large-scale retrospective studies from industry platforms that used self-monitoring (85)(86)(87)(88)(89).…”
Section: Key Findingssupporting
confidence: 87%
“…Multiple digital tools (websites, mobile applications, wearables, electronic scales; see [ 33 ]) are available for self-monitoring, with mobile applications enabling photo-based meal logs. Meal logging has been shown to be associated with higher weight loss in two retrospective analyses [ 23 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“… 48 In line with our findings, weight loss via an app using a photo feature as a dietary record method showed that a greater weight loss is mediated by increased duration and logged days. 49 Notably, several dietary-based programs for weight loss demonstrated that greater initial weight loss is associated with a lower study dropout rate. 50–54 Initial weight loss is a known predictor of successful weight loss and greater initial weight loss may be the motivating factor leading to longer treatment length and less attrition.…”
Section: Discussionmentioning
confidence: 99%